Anchorage loss and root resorption associated with two anchorage reinforcement methods in a dog model - Al-Awadhi, Ebrahim (Trinity College (Dublin, Ireland). School of Dental Science, 2012)
Intra-oral anchorage reinforcement methods are crucial for the success and outcome of orthodontic treatment. This thesis reports on the efficacy of two different types of intra-oral anchorage reinforcement methods; Nance appliance and miniscrews, and their effect on orthodontically induced inflammatory root resorption (OIIRR). The aim of the first study was to examine the amount of anchorage loss (AL) and desired tooth movement (DM) found in the Nance appliance group compared with the control group (conventional molar anchorage) at 3 time points (5, 10 and 15 weeks). Four beagle dogs were fitted with a custom made Nance appliance and bands on the mandibular fourth (PM4) and second (PM2) premolar, respectively. The control beagle dogs (n=3) were fitted with bands on the PM2 and PM4. Reference miniscrews were placed mesial to the PM2 to measure the amount of tooth movement. The PM2 was retracted over 15 weeks in both groups (Nance and control) and the amount of PM4 (AL) and PM2 (DM) movement was recorded at each time point. The mean amount of DM was significantly (p=0.03) more in the Nance group than the control group at 10 weeks, but was not different after 15 weeks. The mean percentage of AL to the total space closure in the Nance group was 28.8%. The Nance appliance had 16.9% less AL than the control group after 15 weeks (p=0.03). Most of the Nance appliance’s AL (80%) occurred over the first 10 weeks. In the second study, the mean AL and DM, at 3 time points (5, 10 and 15 weeks), was compared between the miniscrew anchorage reinforcement group and the control group (conventional molar anchorage). Beagle dogs (n=6) were fitted with custom made bands on the mandibular PM2 and PM4. Reference miniscrews were used as described earlier to measure the amount of movement at the different time points. In the miniscrew group (n=3), active miniscrews were placed buccal and mesial to the PM4 to apply distal traction to the PM2. The mean amount of DM was significantly (p=0.03) more in the miniscrew than the control group at 10 weeks, but was not different after 15 weeks. The mean percentage of AL in the miniscrew group (miniscrew movement) was 15.7% of the total movement. The mean amount of AL was 0.92 mm. The miniscrew group had 30% less AL than the control group (p<0.01). Most of the miniscrews’ AL (70%) occurred over the first 5 weeks.
Keywords: Dental Science, Ph.D.; Ph.D. Trinity College Dublin